COVID-19 triggering homecare professionals' change of attitudes towards e-Welfare - Päivikki Kuoppakangas; Juha Lindfors; Jari Stenwall; Tony Kinder; Antti Talonen (Finnish Social and Health Informatics Association, 2020)
During 2020, the COVID-19 crisis expanded the use of digital tools in public health and social care. The aim of this qualitative, single-case study was to scrutinize how homecare professionals experienced meaningfulness in their work in the midst of a crisis and with the utilization of the videophone in long-term homecare service provision. The empirical data consisted of 20 thematic interviews carried out among homecare professionals and their managers in the city of Tampere, Finland. The results indicated that the videophone can generate significance, self-realization and broader purposes among homecare professionals, thus providing meaningfulness for work in the midst of a crisis and continuous work-related changes. In addition, a crisis may support change in the meaningfulness of e-welfare in work-related tasks and aid in overcoming reluctance amongst public-sector social care (homecare) professionals towards an e-welfare initiative: the videophone (VideoVisit).